A rock magnetic record from Lama Lake, Taymyr Peninsula, northern Central Siberia. - Nowaczyk, Norbert R; Harwart, Stefanie K; Melles, Martin (PANGAEA, 2000)
An 11 m long sediment core ftorn Lama Lake, Northern Siberia, has been subjected to intense sedimentological, geochemical and rock magnetic analyses. According to a palynologic investigation the recovered sediments cover the whole Holocene and the late Pleistocene reaching back to about 17 ka. IRM acquisition experiments, hysteresis loop and back field as well as thermomagnetic measurements revealed magnetite in the pseudo-single domain range as the only remanence carrier. Sharp rock magnetic boundaries occur at 20 and 745 cm sub-bottom depth that are clearly linked to shifts in the median grain size of the magnetite. These boundaries are close to the present boundaries that bracket an anoxic zone between the subrecent and a late Pleistocene oxic section of the sediments. Within the anoxic section, magnetites are characterized by significantly larger median grain sizes but within a very narrow grain size range. The shift from fine grained magnetite within the oxic sediments to coarse grained magnetite is interpreted as the result of dissolution of the finest magnetite grains within the anoxic sediments. A significant shift of the Ti/Fe-ratio of the bulk sediment at a sub-bottom depth of 735 cm does not correspond to thermomagnetic properties, i.e. Curie-temperatures do not follow the variable Ti-content of the sediment.
Rock magnetic record from Lama Lake
Keywords: AWI_PerDyn; COMPCORE; Composite Core; GeoForschungszentrum Potsdam; GFZ; Norilsk/Taymyr, Sibiria; Norilsk/Taymyr93; Permafrost Research (Periglacial Dynamics) @ AWI; PG1111; Quaternary Environment of the Eurasian North; QUEEN; Sampling/drilling in lake